The Effect of Madihin Culture as a Medium of Political Communication in Banjarmasin Election 2024 - Muzahid Akbar Hayat; Sri Wahyuni; Misna Misna; Achmadi Achmadi; M. Riki (International Journal of Law, Environment, and Natural Resources, 2022)
The objectives to be achieved in this research are to find out how the regulation regarding the level of compliance with turning on the motorcycle headlights during the day and how the effectiveness of the motorcycle headlights obligation during the day reduces the number of motorcycle accidents. The research method used is an empirical legal research method called field research, by interviewing informants and knowing respondents' perceptions which are then compared to conclude. The study results show the regulation regarding compliance with turning on the motorcycle headlights and how the effectiveness of the motorcycle's headlight obligation during the day reduces the number of motorcycle accidents. Based on the results of research conducted by researchers, it can be concluded that, in Law Number 22 of 2009 concerning Road Traffic and Transport Article 107 paragraph (2) regarding compliance with turning on the leading lights during the day for two-wheeled drivers to reduce the number of accidents in the jurisdiction of the City Police. Banjarmasin is ineffective even though the number of compliance violations with turning on the leading lights during the day for two-wheelers is decreasing.